2020
DOI: 10.21203/rs.3.rs-34729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic value of Cardiac Biomarkers in COVID-19 Infection: A Meta-analysis

Abstract: BackgroundMultiple Biomarkers have recently been shown to be elevated in COVID-19, a respiratory infection with multi-organ dysfunction; however, information regarding the prognostic value of cardiac biomarkers as it relates to disease severity and cardiac injury are inconsistent.Research QuestionThe goal of this meta-analysis was to summarize the evidence regarding the prognostic relevance of cardiac biomarkers from data available in published reports.Study Design and MethodsPubMed was searched from inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
1
19
1
2
Order By: Relevance
“…Weight loss in COVID‐19 patients has been found to positively correlate with higher CRP levels, reduced kidney function, and longer duration of disease 6 . Possible associations likely also include abnormal markers of cardiac and kidney function in COVID‐19, 31,32 as cachexia in acute and in chronic COVID‐19 disease may also develop as a secondary consequence of cardiac and renal problems. Therapies that prevent cardiac and renal events may therefore also be useful in the short‐term and long‐term care of patients with COVID‐19 or after COVID‐19 acute illness.…”
Section: Predictors Of Cachexia In Covid‐19mentioning
confidence: 99%
“…Weight loss in COVID‐19 patients has been found to positively correlate with higher CRP levels, reduced kidney function, and longer duration of disease 6 . Possible associations likely also include abnormal markers of cardiac and kidney function in COVID‐19, 31,32 as cachexia in acute and in chronic COVID‐19 disease may also develop as a secondary consequence of cardiac and renal problems. Therapies that prevent cardiac and renal events may therefore also be useful in the short‐term and long‐term care of patients with COVID‐19 or after COVID‐19 acute illness.…”
Section: Predictors Of Cachexia In Covid‐19mentioning
confidence: 99%
“…A presentation on the current worldwide pandemic caused by COVID-19 was given by 23 . Considering the above conclusion, we believe early diagnosis and treatment will be much important to improve the prognosis of ACI patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a meta-analysis including 1664 patients illustrated that ACI could occur in one third of patients with COVID-19 22 . More than one studies have demonstrated that Cardiac injury was independently associated with significantly increase of mortality 22, 23 . Considering the above conclusion, we believe early diagnosis and treatment will be much important to improve the prognosis of ACI patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports from China suggest that cTn values > 99 th percentile of the upper normal limit (ULN) are powerful predictors of poor outcomes and mortality in COVID-19 patients 5 , 6 , 13 . However, a recent meta-analysis of studies comparing cTn levels in patients who were critically ill to those who were not demonstrated no significant differences between cTn levels 14 . Finally, the impact of elevated cTn on the outcomes in COVID-19 patients is not well studied and characterized 15 , 16 , 17 , 18 , 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%